The role of the classical renin–angiotensin system and angiotensin-converting enzyme 2/Ang(1–7)/Mas axis in pulmonary fibrosis - Lang, Changhui; Huang, Bo; Chen, Yan; He, Zhixu (Frontiers in Medicine, 2025)
Pulmonary fibrosis (PF), a progressive and fatal disease, is characterized by fibroblast proliferation, excessive extracellular matrix deposition, and collagen synthesis. These pathological changes lead to impaired lung structure and function, ultimately resulting in respiratory failure. Emerging basic and clinical evidence highlight the renin–angiotensin system (RAS) as a critical contributor to PF onset and progression. Angiotensin (Ang) II, a key RAS component, mediates various biological effects through its receptors, Ang II receptor type 1 (AT1R) and Ang II receptor type 2 (AT2R). Ang II promotes vasoconstriction, inflammation, and fibrosis via AT1R, while it shows contrasting effects through AT2R. Angiotensin-converting enzyme 2 (ACE2) plays a significant role in RAS by converting Ang II into Ang (1–7), which in turn interacts with Mas receptor and Mas-associated G-protein-coupled receptor D to exert anti-inflammatory, anti-apoptotic, and anti-fibrotic effects. The RAS also influences autophagy, oxidative stress, and inflammation in the progression of PF. This review provides an updated overview of the roles of the classical and non-classical RAS pathways in PF.